Management of Periprosthetic Infection: Review of Current Literature and Management Algorithm - Puchol, Joan Olucha; Aviñó, Luis Díaz; Paula, Prario Massimino (Revista Chilena de Ortopedia y Traumatología, 2025)
Objective This article provides a comprehensive review of periprosthetic joint infection management, evaluating the latest international consensus and guidelines to establish an effective therapeutic approach for these complex infections.Materials and Methods Therapeutic strategies, including Debridement, Antibiotics, Implant Retention (DAIR), one- and two-stage revisions, and antibiotic-loaded spacers, were analyzed. Predictive scales like CRIME80 and KLIC assess failure risks to guide clinical decision-making.Results DAIR has shown approximately 71% success in acute infections when specific criteria, such as limited symptom duration and antibiotic-susceptible microorganisms, are met. The CRIME80 and KLIC scales provide predictive value in determining the risk of failure. For selected patients, one-stage revision offers advantages, while the two-stage procedure remains the gold standard for complex cases.Discussion The data emphasizes the importance of a multidisciplinary approach, integrating input from microbiology, infectious disease specialists, and surgical teams to personalize treatments and improve outcomes.Conclusions Effective management of periprosthetic infections requires a biofilm-focused approach incorporating predictive scales and recent diagnostic and surgical advances. A well-coordinated, evidence-based approach enables improved clinical results and better patient quality of life.Evidence level: IV.
Keywords: periprosthetic joint infection; DAIR; two-stage surgical revision; one-stage surgical revision; hip arthroplasty infection